Impact Analysis of Condongcatur Underpass Development Plan with Macro Traffic Simulation PTV VISUM on Road Network Performance - Yusup, Muhamad; Munawar, Ahmad; Irawan, Muhammad Zhudy (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
It is planned to build an Underpass for the Condongcatur intersection to improve traffic performance and overcome the congestion that occurs. The purpose of this research is to analyze the existing traffic performance around the Condongcatur Underpass construction area, predict the impact caused, and formulate efforts to handle traffic impacts and analyze how effective the construction of the Condongcatur Underpass is in overcoming congestion that occurs. This research uses a transportation model approach to analyze the road network using PTV VISUM software. The results of the research on existing conditions show the performance of the affected road network with a v/c ratio value between 0.21 - 1, 23 (Level of service B - F). At the time of construction there were 12 road sections most affected by the Condongcatur Underpass construction plan, where the road section with the highest percentage increase occurred on the Padjajaran road section by 167% which was originally in service category C to F. In operational conditions, the Padjajaran Road section with the Underpass is in the B and C service level categories. The performance results on the affected road network provide better results with the Underpass compared to the existing conditions.